A collection of documents on Spitzbergen and Greenland : comprising a translation from F. Martens' Voyage to Spitzbergen : a translation from Isaac de la Peyrère's Histoire du Groenland and God's power and providence in the preservation of eight men in Greenland nine months and twelve days /: comprising a translation from F. Martens' Voyage to Spitzbergen : a translation from Isaac de la Peyrère's Histoire du Groenland and God's power and providence in the preservation of eight men in Greenland nine months and twelve days. (2017) - Unknown
No abstract available